International migration and Africa: South-North or South-South logic? - (:unkn) unknown (My University, 2020)
International migrations for Africa cover two geographical areas. The first, South-North, can be explained by the desire of people to improve their living conditions and by historical links, in a context where the governance of African countries create many development challenges. The second concerns the African intra-continental migrations South-South whose analysis can lead to highlight nature
Keywords: African Research